2020
DOI: 10.1073/pnas.1917289117
|View full text |Cite
|
Sign up to set email alerts
|

On-demand modulation of 3D-printed elastomers using programmable droplet inclusions

Abstract: One of the key thrusts in three-dimensional (3D) printing and direct writing is to seamlessly vary composition and functional properties in printed constructs. Most inks used for extrusion-based printing, however, are compositionally static and available approaches for dynamic tuning of ink composition remain few. Here, we present an approach to modulate extruded inks at the point of print, using droplet inclusions. Using a glass capillary microfluidic device as the printhead, we dispersed droplets in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…In the context of technology development, DASP is different from existing 3D printing techniques for manipulating spherical objects such as droplets and spheroids. For example, in embedded droplet printing, individual droplets are dispensed far apart from each other to form discrete patterns [17,40] or randomly stacked together to form thick structures [41] . By contrast, DASP enables on-demand deposition of individual bio-ink droplets at prescribed locations to form integrated, organized structures.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of technology development, DASP is different from existing 3D printing techniques for manipulating spherical objects such as droplets and spheroids. For example, in embedded droplet printing, individual droplets are dispensed far apart from each other to form discrete patterns [17,40] or randomly stacked together to form thick structures [41] . By contrast, DASP enables on-demand deposition of individual bio-ink droplets at prescribed locations to form integrated, organized structures.…”
Section: Discussionmentioning
confidence: 99%
“…Precise control over the printing pattern combined with its relative simplicity and the wide range of applications make DBB a very appealing printing technology. For example, DBB allows the fabrication of bifurcated tubular structures and thus enables bioprinting of vascular networks [ 33 ]. Currently, droplet sizes of 25 to 300 µm can be controlled [ 34 ].…”
Section: Printing Methodsmentioning
confidence: 99%
“…To meet the demands, the combination of microfluidics and 3D printing is emerging as a powerful tool, which provides a simple and flexible control over the emulsification process. [ 30–35 ] For example, continuous extrusion of liquid metal in carbopol hydrogel via a 3D printing system allows the design and construction of 3D structures and electronic systems; [ 36 ] elastomers with tunable compositions and properties are prepared using the combined technique; [ 37 ] biomimetic systems with synergetic color and shape responses are developed using microfluidic 3D printing. [ 38 ] The progresses have demonstrated that microfluidic 3D printing is suitable to serve as a platform for the design and development of functional materials.…”
Section: Introductionmentioning
confidence: 99%